RELEVANSI FALSAFAH ORANG TENGGER TENTANG KEBAHAGIAAN TERHADAP UPAYA PENDIDIKAN KARAKTER BANGSA - Mohammad Bahrul Ulum (Nurul Jadid University, 2016)
Against the understanding that the deep-rooted moral wisdom in Tenggerese life can be an alternative way of view amid the cur- rent multidimensional crisis, it aims to construct the theoretical constructs of the concept of happiness in Tengger’s view and how relevant it is to the nation’s character education efforts. The the- oretical constructions are done by using Aristotelian ethical theory (eudaimonisme) as a way of looking at the ethical values in the life of the Tenggerese.This research is a literature study (library research). Aristotelian ethics is the formal object of research, while its material object is the Tenggerian view of the nature of happiness. The methods used are induction, interpretation, and comparison. The method is used to analyze the meaning of happiness in Tengger’s view which is then reviewed from the perspective of the ethics of Aristotle’s happiness.Happiness in the Tenggerian view implies a state of equilibrium in total religiosity, so happiness can be called the ultimate goal of all the realities of this nature. Aristotle sees happiness as a “fullness” whose value can not be restricted (without qualifica- tion). Achievement is done by realizing the full human potential (rationality) in full and accompanied by the virtues (areté). The concept of Tenggerese happiness has a structural similarity to the concept of happiness in Aristotelian ethics. The Tenggerese, like Aristotle, see that happiness is not an instrumental purpose, but the ultimate goal of all human action. The Tengger people see a “tri-singular” relation in life, in a social, natural and spiritual context. On the basis of this relationship pattern then the main life is to keep the harmony alive. This view of the principle of har- mony then produces ethical virtues that are consistent with the principle (respect, harmony and simplicity). These virtues are the source of all good in life and, in the context of character educa- tion of the nation, these virtues can be a foothold and-especially- an example of what and how the character of this nation is built.